Analog Memristor of Lead‐Free Cs4CuSb2Cl12 Layered Double Perovskite Nanocrystals as Solid‐State Electronic Synapse for Neuromorphic Computing (Adv. Mater. Interfaces 30/2022). Issue 30 (26th October 2022) - Parveen, Sumaiya; Manamel, Litty Thomas; Mukherjee, Arka; Sagar, Srikrishna; Das, Bikas C.
Abstract : Neuromorphic Computing Thin‐film of lead‐free caesium copper antimony chloride (Cs4 CuSb2 Cl12 ) layered double perovskite nanocrystals is utilized to demonstrate robust electroforming free analog resistive switching with synaptic functionalities and neural activities, as depicted in article number 2200562 by Sumaiya Parveen, Bikas C. Das, and co‐workers.